(untitled) (Papeles, 2012)
The research is the intention of identifying the conceptions of assessment of students in the teacher education process in physical education. As a starting point we examine the issue of evaluation in the context of the school from the latest thinking on the subject, trying to point out as the specific conditions educational institutions, have caused significant changes in the curricula of the different areas of knowledge, particularly in physical education; shows how these changes represent new expectations of the discipline as well as new educational requirements of teachers ultimately determine reorientations in their training programs, then, is from this scenario justifying the need to diagnose the current state of the problem of the evaluation in licensed training programs in physical education, understood as a competence inherent in the teaching profession regardless of their disciplinary field, with the point of his analysis relevance and consistency with educational bets of each training program and especially with the demands of a changing society.